2022
DOI: 10.1080/21655979.2022.2061283
|View full text |Cite
|
Sign up to set email alerts
|

CircSETD3 (hsa_circ_0000567) inhibits proliferation and induces apoptosis in cholangiocarcinoma cells via downregulation of microRNA-421 expression

Abstract: Cholangiocarcinoma (CCA) is a fatal tumor associated with chronic inflammation. Circular RNAs (circRNAs) have been evidenced to be involved in tumorigenesis and tumor progression. This study aimed to explore the effects and potential molecular mechanism of circSETD3 in CCA progression. Levels of CircSETD3 and microRNA (miR)-421 in CCA tissue and cell lines were measured using quantitative real-time polymerase-chain reaction (qRT-PCR). A direct target of miR-421 was predicted using TargetScan and further confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The current study identified the reduced expression of ENTPD3-AS1 in LUAD patients, who have poor clinical outcomes, supporting that ENTPD3-AS1 could act as a promising prognostic predictor in LUAD. miR-421, which is an oncomir associated with various cancers, including pancreatic cancer, cholangiocarcinoma, and LUAD [22][23][24], is sponged by ENTPD3-AS1. Indeed, the knockdown of ENTPD3-AS1 or miR-421 inhibitors decreased cell proliferation, enhanced cell migration and epithelial phenotype transition in A549 cells, supporting the findings that ENTPD3-AS1 inhibited the oncogenic function of miR-421 in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…The current study identified the reduced expression of ENTPD3-AS1 in LUAD patients, who have poor clinical outcomes, supporting that ENTPD3-AS1 could act as a promising prognostic predictor in LUAD. miR-421, which is an oncomir associated with various cancers, including pancreatic cancer, cholangiocarcinoma, and LUAD [22][23][24], is sponged by ENTPD3-AS1. Indeed, the knockdown of ENTPD3-AS1 or miR-421 inhibitors decreased cell proliferation, enhanced cell migration and epithelial phenotype transition in A549 cells, supporting the findings that ENTPD3-AS1 inhibited the oncogenic function of miR-421 in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies highlight the implication of microRNAs (miRNAs) in cancer research, as they play an important role in regulating cancer cells and impacting various aspects of cancer progression, including apoptosis induction, cell cycle regulation, metastasis promotion, and angiogenesis stimulation [30,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. In a recent investigation by Xiong et al [79], the effects of circSETD3, a circular RNA containing multiple miRNA binding sites, were studied in CCA cells. The experimental research also focused on miR-421, which was described to promote cell proliferation in human gastric cancer.…”
Section: Potential Therapeutical Approachesmentioning
confidence: 99%
“…circSETD3 has been implicated in CCA progression. [79] miR-421 It promotes cell proliferation in human gastric cancer and represents a promising therapeutic target for CCA treatment. [80,81] miR-373 Its overexpression promotes apoptosis in CCA cells by targeting ULK1.…”
Section: Molecule Function References Circsetd3mentioning
confidence: 99%
“…For example, cerebellar degenerative-related protein-1 antisense (CDR1as), which has been extensively studied in multiple cancer types, 10 can serve as a biomarker for ICC. 11 Similarly, circ_0005230, 12 circDNM3OS, 13 circ-LAMP1, 14 circ0021205, 15 circRTN4IP1, 16 and circSETD3 17 can promote the proliferation, growth, or metastases of ICC. circ_0020256, 18 which is associated with the tumor microenvironment, is an exosomal circRNA produced by tumor-associated M2 macrophages and promotes cancer progression.…”
Section: Introductionmentioning
confidence: 99%